Pollution of Water from Urban, Agricultural and Industrial Effluent: A Review - Wahid Ali Hamood Altowayt (Progress in Engineering Application and Technology, 2022)
Currently, water resources are becoming increasingly limited, and many are contaminated by human causes such as industrial waste, agricultural waste, and domestic waste. As a result, wastewater treatment is still required before it may be discharged into natural water sources. The primary goal of wastewater treatment is to eliminate impurities such as suspended particles, organic carbon, nutrients, inorganic salts, heavy metals, pathogens, and other toxins found in wastewater. Wastewater treatment’s main purpose is to safeguard human health and the environment. In this review, the most prevalent contaminant from urban, agricultural, and industrial effluents have been outlined to assist in selecting the most effective ways to adequately treat the various types of wastewater.